Pelatihan Penyusunan Bahan Ajar Berbasis Multimedia Bagi Guru-Guru Yayasan Ali Imron Pakamban Sumenep - Jauhari, Mohammad Nafie; Juhari, Juhari; Jamhuri, Mohammad (JRCE (Journal of Research on Community Engagement), 2020)
Learning media is a useful tool and intermediary for facilitating the teaching and learning process to streamline communication between teachers and students. This community service activity is divided into three main activities, namely the delivery of concepts or theories of multimedia, types of multimedia, the use of multimedia, and making presentations using practical and interactive PowerPoints tools; second, training on how to use PowerPoint effectively; and third, evaluation on the ability of training participants in making multimedia-based teaching materials.